COVID-19: Analysing the Principle and Application of Iʿtibār Ma’ālāt in the Selected Fatwas Issued by the Malaysian National Council for Islamic Religious Affairs (MKI) - Abdul Manan Ismail; Ahmad Syukran Baharuddin; Muhammad Hazim Ahmad (IIUM Press, International Islamic University Malaysia, 2024)
About 650 years ago, al-Shāṭibī advocated new reforms on Uṣūl al-Fiqh with the introduction of some novel legal theories. The principle iʿtibār ma’ālāt was among the legal theories he proposed in his magnum opus, al-Muwāfaqāt. However, due to some complicity, his theories received little attention and remain stagnated. In fact, few classical jurists have previously paid attention to the principle of iʿtibār ma’ālāt. Nonetheless, in accordance with the development of the discipline of maqāṣid al-sharīʿah, the discussion on the principle of ma’ālāt, which was previously stagnated, has recently begun to gather traction among researchers worldwide in general, as well as in Malaysia in particular. Interestingly, al-Shāṭibī’s theory is applicable in solving several emerging religious concerns, particularly, in the event of COVID-19 pandemic. Several fatwas have been issued at the national as well as state levels in Malaysia to curb this pandemic. In this qualitative study, several fatwas issued by the Malaysian National Council for Islamic Religious Affairs (MKI) has been selected to analyse the principle and application of iʿtibār ma’ālāt. This study explores the principle and application of iʿtibār ma’ālāt which was implicitly and explicitly applied in each fatwa selected. Furthermore, this indicated that the MKI has successfully implemented the principle in issuing fatwas responding to the emerging religious issues.